2010
DOI: 10.5194/acp-10-11471-2010
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible loss of ice nucleation active sites in mineral dust particles caused by sulphuric acid condensation

Abstract: Abstract. During the FROST-2 (FReezing Of duST) measurement campaign conducted at the Leipzig Aerosol Cloud Interaction Simulator (LACIS), we investigated changes in the ice nucleation properties of 300 nm Arizona Test Dust mineral particles following thermochemical processing by varying amounts and combinations of exposure to sulphuric acid vapour, ammonia gas, water vapour, and heat. The processed particles' heterogeneous ice nucleation properties were determined in both the water subsaturated and supersatur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
189
6

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 187 publications
(208 citation statements)
references
References 60 publications
(112 reference statements)
13
189
6
Order By: Relevance
“…As we can see, the hygroscopicities for the inorganic compounds (SA, AbS, AS) in Table 2 are substantially higher than the ones for organic species. It should be noted that there are two reported kappa vales for SA particles (0.7 and 0.9: Sullivan et al, 2010;Petters and Kreidenweis, 2007). When the theoretical SA kappa value is reduced by the effect of the residual water in the dry particles in HTDMA measurements the value is close to 0.7.…”
Section: Volume Fractions Of Organics (ε O ) and Of Sa (ε Sa )mentioning
confidence: 96%
See 2 more Smart Citations
“…As we can see, the hygroscopicities for the inorganic compounds (SA, AbS, AS) in Table 2 are substantially higher than the ones for organic species. It should be noted that there are two reported kappa vales for SA particles (0.7 and 0.9: Sullivan et al, 2010;Petters and Kreidenweis, 2007). When the theoretical SA kappa value is reduced by the effect of the residual water in the dry particles in HTDMA measurements the value is close to 0.7.…”
Section: Volume Fractions Of Organics (ε O ) and Of Sa (ε Sa )mentioning
confidence: 96%
“…Biskos et al (2009) also reported the reduced hygroscopic properties for the SAparticles smaller than 36.1 nm based on partial neutralisation because of contaminant NH 3 in the experimental HTDMA set-up. Hence, we use the value 0.7 for the kappa value of SA particles (Sullivan et al, 2010). With known O:C ratio the organic hygroscopicity (κ o ) can be explicit from previous measurements by Massoli et al, 2010 (e.g. at O:C 0.1 it is 0.05).…”
Section: Volume Fractions Of Organics (ε O ) and Of Sa (ε Sa )mentioning
confidence: 99%
See 1 more Smart Citation
“…ATD can possibly be more ice nucleation active than natural desert dust, either due to its enhanced roughness resulting from milling or due to its different mineralogical composition . Another reason for lower activity of natural dust particles is related to their aging processes in the atmosphere, which may reduce their ice nucleation ability (Sullivan et al, 2010).…”
Section: Y Wang Et Al: Different Contact Angle Distributionsmentioning
confidence: 99%
“…That study also demonstrated that due to the differences in scattering, each of the 13 dust types measured could be grouped according to their individual optical properties. In addition, mineral dusts facilitate the nucleation of ice by acting as heterogeneous ice nuclei (DeMott et al 2003;Archuleta et al 2005;Fornea et al 2009;Sullivan et al 2010;Murray et al 2012). …”
Section: Introductionmentioning
confidence: 99%